Effects of Wall Properties on Temperature-Control Effectiveness of Heating Section in a Thermosiphon Containing PCM Suspensions - Ching-Jenq Ho; Shih-Ming Lin; Rong-Horng Chen; Chi-Ming Lai (Applied Sciences, 2020)
This article considers the problem of natural heat transfer in a rectangular thermosiphon to investigate the effects of wall properties (thickness and thermal conductivity) on the heat-transfer characteristics of phase-change-material (PCM) suspension flow. The following parameter ranges were investigated: dimensionless loop-wall thickness, 0–0.5; wall-to-fluid thermal-conductivity ratio, 0.1–100; modified Rayleigh number, 1010–1011; and volumetric fraction of PCM particles, 0–10%. From numerical simulations via the finite-volume approach, it was found that using a pipe with appropriate wall thickness and thermal conductivity containing PCM suspensions for the heating section of a rectangular thermosiphon can effectively control the maximal temperature.